Real interest rate parity : evidence from East Asian economies relative to China - Venus, Khim-Sen Liew; Ling, Tai-Hu (Universiti Malaysia Sabah (UMS), 2008)
This study examines the real interest rate parity (RIP) hypothesis in the case of East Asian economies by taking China as foreign counterpart. Results obtained from panel unit root tests are in line with previous findings that are supportive of the hypothesis. The estimated half-life of the RIP deviations is 3.21 quarters, indicating RIP holds strongly in this region with respect to China. This implies that the choices and effectiveness of the monetary and fiscal policies in the East Asian economies will be very much influenced by the external factors originating from China, in additional to Japan and US as identified in other studies. Furthermore, judging from the another finding of this study that East Asian economies is more integrated with Japan than China, China has yet to further liberalize its financial system before it can overtake Japan as leading financial centre or as anchor country for common currency area in this region.